The Difference Of The Triangular Theory Of Love In Married Women Judging From The Length Of Marriage - Elisa Muloko; Ribka Limbu; Dian Lestari Anakaka (Journal of Health and Behavioral Science, 2020)
One of the main reasons people getting married is because of the love and commitment that is shared with the partner. Sternberg (in Taylor, dkk, 2009), explained that love has three main components, namely intimacy, passion and commitment. This study aims to determine whether there are differences in intimacy, passion and commitment in married women judging from length of marriage. The theory used to explain intimacy, passion and commitment in this study is the Triangular Theory love proposed by Sternberg (1986). This study was conducted at 402 married women. The sampling technique used was purposive sampling. Data collection devices are questionnaire, in the form of the triangular theory of love scale (STLS) adapted by the authors, with the reliability of the scale is 0.956. The results of the data analysis with the Kruskal Wallis technique, obtained value of Asymp. Significance is 0.026 (p < 0.05). The results of the data analysis show that there is a significant differences of intimacy, passion and commitment in married women judging from the length of marriage.